Filipino bands performing in hotels, clubs and restaurants in Asia purveyors of transnational culture in a global arena. - Ng, Stephanie Sooklynn
My research is on a group of entertainers who constantly travel for work purposes. Since performing abroad is how they make a living, most would prefer to remain abroad for as long as possible because returning to the Philippines would mean unemployment for them. Hence, I found it necessary to "follow the people" (Marcus 1995:106) in order to chart the impact of of Filipino musicians on others as well as to discover how traveling has influenced them. In the course of one year from October 2003-October 2004, I carried out fieldwork in several cities in East and Southeast Asia. My work conducted in urban spaces, the "global cities" (Saskia Sassen 1991) where international flows of people, money, technology and the mass media as cultural centers that influential in shaping economic and policies in the region. through multi-locale ethnography, I planned to identify song links between these various sites in which Filipino entertainers perform.